2014
DOI: 10.1007/s00280-014-2548-z
|View full text |Cite
|
Sign up to set email alerts
|

First-line gefitinib therapy for elderly patients with non-small cell lung cancer harboring EGFR mutation: Central Japan Lung Study Group 0901

Abstract: First-line gefitinib therapy is effective and feasible for elderly patients harboring EGFR mutation, and improves disease-related symptoms, especially pulmonary symptoms like shortness of breath and cough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…However, these clinical trials were usually conducted only or mainly in healthy patients aged 75 years or younger. In elderly patients with advanced EGFR-mutated NSCLC, some reports [13][14][15] showed the efficacy and safety of gefitinib. However, to our knowledge, the antitumor effects and safety profiles of erlotinib focused on elderly patients have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…However, these clinical trials were usually conducted only or mainly in healthy patients aged 75 years or younger. In elderly patients with advanced EGFR-mutated NSCLC, some reports [13][14][15] showed the efficacy and safety of gefitinib. However, to our knowledge, the antitumor effects and safety profiles of erlotinib focused on elderly patients have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, epidermal growth factor receptor (EGFR) mutations, such as exon 19 deletion and L858R point mutation, are well recognized as driver mutations and promising predictors of the efficacy of EGFR tyrosine kinase inhibitors (TKIs), such as gefitinib, erlotinib, and afatinib, in NSCLC patients harboring EGFR mutations [3][4][5][6][7]. In addition, EGFR-TKIs are recommended for elderly people [8][9][10] and they are effective regardless of the treatment timing in patients with NSCLC harboring EGFR mutations [11,12]. Recently, a large cohort study reported that gefitinib therapy resulted in a 5-year survival rate of approximately 20% in NSCLC patients harboring…”
Section: Introductionmentioning
confidence: 99%
“…The ORR was 70%, the disease control rate (complete response, partial response and stable disease) was 90% and the median PFS time was 10 months; the functional assessment of a cancer therapy-lung cancer subscale questionnaire recorded a significant improvement in the first four weeks of treatment, particularly for dyspnea and cough (18).…”
Section: Activity Of Gefitinib and Erlotinibmentioning
confidence: 99%
“…The majority of significant retrospective data are obtained by subgroup analysis of elderly patients from the large studies performed without age restriction (12)(13)(14). To date, a lower contribution has been provided from prospective studies specifically designed to evaluate the efficacy and safety of molecular-targeted drugs in elderly patients with NSCLC (15)(16)(17)(18)(19)(20)(21). The aim of the present review is to summarize the current data on the efficacy and safety of molecular-targeted therapy in elderly patients with advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%